Budgetary Impact of 20-Valent Pneumococcal Conjugate Vaccine Use for Adult Expatriates Living in Dubai - Mostafa Zayed, MSc; Jean Joury, BS Pharm, CMD; Mohamed Farghaly, FRCGP; Sara Al Dallal, MD, MSc; Bassam Mahboub, MD; Emily Kutrieb, BA; Ahuva Averin, MPP (Current Therapeutic Research, 2023)
ABSTRACT: Background: Dubai Health Authority currently recommends sequential administration of 13-valent pneumococcal conjugate vaccine (PCV13) followed by (→) 23-valent pneumococcal polysaccharide vaccine (PPV23) to prevent pneumococcal disease among adults at elevated risk of illness. Despite recommendations, disease burden and associated costs remain substantial. A new 20-valent pneumococcal conjugate vaccine (PCV20) recently received regulatory approval in the United Arab Emirates and has the potential to further reduce burden of pneumococcal disease. Objectives: To evaluate budget impact of use of novel PCV20 compared with current recommendations (ie, PCV13→PPV23) among expatriates in Dubai aged 50 to 99 years and those aged 19 to 49 years with risk factors. Methods: A deterministic model depicted 5-year risks and costs of invasive pneumococcal disease and all-cause nonbacteremic pneumonia. Each year of the modeling horizon, persons could be vaccinated with either PCV20 or PCV13→PPV23 or remain unvaccinated; persons vaccinated during the modeling horizon were not eligible for vaccination in subsequent years. Annual vaccine uptake was assumed to be 5% in base cases analyses; higher uptake was considered in scenario analyses. Costs were discounted at 3.5% annually and reported in US dollars. Results: In base case, use of PCV20 alone would prevent an additional 13 cases of invasive pneumococcal disease, 31 cases of inpatient all-cause nonbacteremic pneumonia, 139 cases of outpatient all-cause nonbacteremic pneumonia, and 5 disease-related deaths compared with PCV13→PPV23. Medical care costs would be reduced by $354,000, and total vaccination costs would decrease by $4.4 million. PCV20 would therefore yield net budgetary impact of –$4.8 million, resulting in savings of $2.47 per-person per-year over 5 years. In scenarios with higher vaccine uptake, PCV20 prevented more cases and deaths and yielded greater budget savings (vs PCV13→PPV23). Conclusions: PCV20 would reduce burden and economic costs of pneumococcal disease among expatriates in Dubai compared with PCV13→PPV23 and would therefore be budget saving for private health insurers who cover the majority of this population.